2020
DOI: 10.31362/patd.685215
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrik non-travmatik koma prognozunu öngörmede klinik, elektroensefalografik ve nöroradyolojik parametrelerin rolü

Abstract: To investigate the early outcome of non-traumatic coma (NTC) in pediatric critical care in relation to the prognostic role of clinical, electroencephalographic, and neuro-radiological factors. Materials and methods: A total of 77 children (means of age: 70.5±68.7 months, 55.8% were boys) with acute encephalopathy, and NTC were included in this retrospective cross-sectional study. Data on patient demographics (age, gender, etiology of NTC) and prognostic factors [Glasgow coma scores (GCS), pupillary light refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…These etiologies are slightly different than those found in Turkey where hypoxic ischemic encephalopathy was as common as CNS infections. [19][20][21][22] In accordance with Gwer et al, 23 our study showed that viral encephalitis was the most common CNS infection. This differs from other studies that revealed a higher frequency of acute bacterial meningitis.…”
Section: Discussionsupporting
confidence: 87%
“…These etiologies are slightly different than those found in Turkey where hypoxic ischemic encephalopathy was as common as CNS infections. [19][20][21][22] In accordance with Gwer et al, 23 our study showed that viral encephalitis was the most common CNS infection. This differs from other studies that revealed a higher frequency of acute bacterial meningitis.…”
Section: Discussionsupporting
confidence: 87%
“…We concluded that, only the presence of abnormal pupillary light reflex was associated with mortality; however, this relationship was insignificant when assessed as an independent risk factor. Previous studies have reported that the absence of pupillary light reflex is associated with unfavorable neurological outcome and mortality [22]. In the present study, the absence of pupillary light reflex and unequal pupillary light reflex findings were evaluated together, which may have caused variations in results.…”
Section: Discussionmentioning
confidence: 97%
“…Among the children with NTC, neuroinfectious etiology was the most common cause of encephalopathy with viral encephalitis being the most frequent diagnosis. A study from Turkey found that hypoxic ischemic encephalopathy (HIE) and neuroinfection were the most common causes of NTC [22]. Similarly, studies from other countries like Pakistan, India, United Kingdom, Nigeria, Malaysia and Saudi Arabia also reported neuroinfection as a leading cause of NTC [4,13,19,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%